2008
DOI: 10.1068/a39107
|View full text |Cite
|
Sign up to set email alerts
|

Are Immigrants' Earnings Influenced by the Characteristics of Their Neighbours?

Abstract: Research and policy contextThe issue of immigration and the resulting ethnic concentrations in some metropolitan neighbourhoods has achieved a salient position in public discourse and policy discussions in Western Europe and the United States alike. In the United States this issue has taken on increased political significance as states and the federal government have considered and sometimes enacted legislative initiatives that would restrict immigration or limit types of social benefits to immigrants already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 42 publications
5
92
2
2
Order By: Relevance
“…It is argued that ethnic minority residents prefer to live close to their own ethnic group and therefore select minority-concentration neighbourhoods (Bolt et al, 2008). There has been a lot of research on the advantages of living in an ethnic enclave, which has been found to be especially advantageous for new immigrants and ethnic minorities with low socioeconomic status (Musterd et al, 2008;Phillips, 2007). It is argued that minorities move to ethnic enclaves because they expect benefits from living among coethnics, such as opportunities for employment (Logan et al, 2002;Zorlu and Mulder, 2008); a familiar culture (Logan et al, 2002); family ties (Hedman, 2013); and social support and a sense of security or belonging (Phillips, 2007).…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…It is argued that ethnic minority residents prefer to live close to their own ethnic group and therefore select minority-concentration neighbourhoods (Bolt et al, 2008). There has been a lot of research on the advantages of living in an ethnic enclave, which has been found to be especially advantageous for new immigrants and ethnic minorities with low socioeconomic status (Musterd et al, 2008;Phillips, 2007). It is argued that minorities move to ethnic enclaves because they expect benefits from living among coethnics, such as opportunities for employment (Logan et al, 2002;Zorlu and Mulder, 2008); a familiar culture (Logan et al, 2002); family ties (Hedman, 2013); and social support and a sense of security or belonging (Phillips, 2007).…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…Living among the own ethnic group is advantageous (Bolt et al, 2008) as co-ethnics can provide opportunities for employment, housing, social security (Logan et al, 2002;Musterd et al, 2008) and a sense of security and belonging (Phillips, 2007). The effect of the neighbourhood ethnic composition on satisfaction will therefore differ between ethnic groups.…”
Section: Ethnic Differences In the Effect Of Neighbourhood Ethnic Commentioning
confidence: 99%
“…In a separate study, Musterd et al (2008) focused on the role of ethnic clusters in relation to immigrants' income development. Differences in immigrant economic trajectories have been attributed to a wide variety of factors.…”
Section: What MIX Matters For Whom and How Much?mentioning
confidence: 99%
“…It was found that neighborhood income characteristics, operationalized by the percentages of adult males with earnings in the lowest 30 th and the highest 30 th percentiles, hold greater explanatory power for individual earnings than domains of neighborhood mix related to education, ethnicity, or housing tenure. Separating the effects of having substantial shares of low and high-income neighbors, it appeared that it is the presence of the share of low income earners that means most for metropolitan and non-metropolitan men and women, with the largest negative effects for metropolitan men.In a separate study, Musterd et al (2008) focused on the role of ethnic clusters in relation to immigrants' income development. Differences in immigrant economic trajectories have been attributed to a Since there is at least a tendency that immigrants settle in enclaves after arrival, and perhaps a tendency that they are staying there for a longer period of time, it makes sense to ask the question whether a concentration of immigrants aids or retards their chances for improving their economic position?…”
mentioning
confidence: 99%